2017
DOI: 10.3892/etm.2017.5066
|View full text |Cite
|
Sign up to set email alerts
|

Renal sympathetic denervation improves myocardial apoptosis in rats with isoproterenol‑induced heart failure by downregulation of tumor necrosis factor‑α and nuclear factor‑κB

Abstract: Chronic congestive heart failure (CHF) is the end outcome of organic heart diseases and one of the major diseases harmful to human health. Renal sympathetic denervation (RSD) is the anatomical basis of transcatheter renal sympathetic nerve ablation within the renal artery. To date, the roles of norepinephrine and angiotensin II (Ang II) in myocardial apoptosis and their underlying mechanisms have not been well explored. The aim of the present study was to verify the hypothesis that RSD is likely to inhibit myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…In our study, we observed reduced levels of sST2 after AMI by immediate RDN, together with changes in IL-33-related remodeling pathways, including reduced activation of NF-κb and expression of TGFβ. The inhibitory effect of RDN on NFκb has been demonstrated previously, which further supports our findings that RDN exerts anti-remodeling effects by the reduction of sST2 and the subsequent modulation of the IL-33/ST2 pathway (34,35).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we observed reduced levels of sST2 after AMI by immediate RDN, together with changes in IL-33-related remodeling pathways, including reduced activation of NF-κb and expression of TGFβ. The inhibitory effect of RDN on NFκb has been demonstrated previously, which further supports our findings that RDN exerts anti-remodeling effects by the reduction of sST2 and the subsequent modulation of the IL-33/ST2 pathway (34,35).…”
Section: Discussionsupporting
confidence: 92%
“…In cultured kidney proximal tubule cells, NE treatment increases poly (ADP-ribose) polymerase 1 (PARP1) and cleaved caspase-3 expression, which is reduced by co-treatment with caspase-3 inhibitor [59]. Consistent with our data, RDNx inhibits renal sympathetic activation, significantly attenuating the expression levels of p53, TNF-α, NF-κB, caspase-2 and -3, and improving apoptosis [146]. On the other hand, activation of α 2 -AR with dexmedetomidine, α 2 -AR agonist attenuates renal cell apoptosis and renal tubule impairment by inhibiting mitochondrial apoptosis pathways in the sepsis-or I/R-induced injury model, which may be effective by regulating NE release [147][148][149].…”
Section: Mechanisms Of Ne-ar Signaling In Aki and Ckdsupporting
confidence: 87%
“…To investigate the effect of AMS on apoptosis, we have studied the protein expression of caspases. Pathological enlargement of the myocardium with isoproterenol results in activation of programmed cell death, compromised contractile function, and eventually heart failure [39]. Besides apoptosis, caspases play an important role in cardiac inflammation.…”
Section: Discussionmentioning
confidence: 99%